Pericarditis mediated by respiratory syncytial virus in a hematopoietic stem cell transplant patient. Issue 4 (3rd June 2013) - Rubach, M.P.; Pavlisko, E.N.; Perfect, J.R.
Abstract We describe a case of pericarditis and large pericardial effusion in a 63‐year‐old African‐American man undergoing autologous hematopoietic stem cell transplant for multiple myeloma. Pericardial tissue biopsy demonstrated fibrinous pericarditis, and immunohistochemistry stains were positive for respiratory syncytial virus. The patient improved with oral ribavirin and intravenous immune globulin infusions.